The Value of Thromboelastography in the Diagnosis of Sepsis-Induced Coagulopathy. (1st September 2020) - Luo, Cuizhu; Hu, Hongbin; Gong, Jian; Zhou, Yun; Chen, Zhongqing; Cai, Shumin
Thromboelastography (TEG) is regularly used for monitoring abnormalities of the coagulation system in patients with sepsis. However, it is unclear whether TEG parameters are associated with sepsis-induced coagulopathy (SIC). Thus, we aimed to assess the diagnostic value of TEG for SIC. The medical records of patients who underwent TEG from January 2016 to December 2016 were analyzed retrospectively. The patients were divided into sepsis group and non-sepsis group. Baseline patient characteristics and coagulation function indexes were compared. Receiver–operating characteristic curve analysis was used to determine predictors of SIC. A total of 167 patients were included, of whom 84 had sepsis. The clot formation speed (K) was significantly higher(P < 0.001), and the maximum amplitude (MA) and angle were significantly lower (both P < 0.001) in the sepsis group than that in non-sepsis group. Patients with SIC had higher Sepsis-related Organ Failure Assessment scores than those patients without SIC (P < 0.001). The area under the curve of K for diagnosing SIC was 0.910. The area under the curve of angle and MA for excluding SIC was 0.895 and 0.882, respectively. Thus, TEG parameters have good diagnostic value for SIC.